Development of a change management competencies framework for public secondary school principals - Casing, Reynaldo Elardo 1968- (University of the Philippines-Diliman, 2020)
The purpose of this research was to find out the development of a change management competencies framework for public secondary school principals in the National Capital Region. It attempted to answer the question, What changes management competencies framework can be developed for public secondary school principals in the National Capital Region? The study used mixed method convergent parallel design and utilized multiple-case study. This research consists of three strands namely: (1) the Quantitative analysis, (2) the Qualitative analysis, and (3) the development of change management competencies model for the public secondary school principals in the National Capital Region. For the quantitative analysis, descriptive and inferential statistics were used while for the qualitative analysis, thematic coding with the use of In Vivo and Atlas Ti. The study shows that the change management competencies of the public secondary school principals are as follows: in terms of school leadership, there were 10 competencies developed; while in terms of instructional leadership, there were six competencies formulated; six competencies were developed in terms of innovation; and lastly, in terms of personal excellence, there were seven developed competencies. Specific implications and recommendations were made based on the finding, and one of this is for the Schools Division Superintendent in his capacity as policy maker should organize a principals development program to enhance the competencies of the principals particularly in change management.